The Efficacy and Safety of Monoclonal Antibody Treatments Against COVID-19: A Systematic Review and Meta-analysis of Randomized Clinical Trials - Ifan Ali Wafa; Nando Reza Pratama; David Setyo Budi; Henry Sutanto; Alfian Nur Rosyid; Citrawati Dyah Kencono Wungu (Interna Publishing, 2023)
Background: The use of monoclonal antibody as the proposed treatment of COVID-19 showed different results in various prior studies, and Efficacy remains open in literature. This study aimed to comprehensively determine the effect of monoclonal antibodies on clinical, laboratory, and safety outcomes in COVID-19 patients. Methods: Sixteen RCTs were analyzed in this meta-analysis using RevMan 5.4 to measure the pooled estimates of risk ratios (RRs) and standardized mean differences (SMDs) with 95% CIs. Results: The pooled effect of Monoclonal antibodies demonstrated efficacy on mortality risk reduction (RR=0,89 (95%CI 0.82-0.96), I2=13%, fixed-effect), Tocilizumab also show efficacy on mortality risk reduction for severe-critical disease (RR=0.90 (95%CI 0.83-0.97), I2=12%, fixed-effect)), need for mechanical ventilation (RR=0.76 (95%CI 0.62-0.94), I2=42%, random-effects), and hospital discharge (RR=1.07 (95%CI 1.00-1.14), I2=60%, random-effects). Bamlanivimab monotherapy did not reduce viral load (SMD=-0.07 (95%CI -0.21-0.07), I2=44%, fixed-effect). Monoclonal antibodies did not differ from placebo/standard therapy for hospital discharge at day 28-30 (RR=1.05 (95%CI 0.99-1.12), I2=71%, random-effects) and safety (RR=1.04 (95%CI 0.76-1.43), I2=54%, random-effects). Conclusion: Tocilizumab should be used for severe to critical COVID-19 because it is not harmful and can improve mortality risk, mechanical ventilation, and hospital discharge. Bamlanivimab-Etesevimab and REGN-COV2 reduced viral load in mild-moderate outpatients.